Component Modification and Data Communication Lines of Automatic Crop Sprinklers on Soil Moisture-Based Agricultural Land - Sujana, Aditya Ilham; Hartawan, Liman (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Plants are living things that need water for their growth. This research was carried out designing, making, and developing tools that previously existed. This development focuses on how to communicate between microcontrollers and aims at the needs of large and open land. Where in previous studies the coverage area was only the area around the radius of the wifi router and the coverage will be increased again using NRF24L01. In previous studies using relays on the solenoid valve will be replaced using Mosfet LR7843 which has lower electrical power requirements. This system uses the Wemos D1 Mini and Arduino Uno as its microcontroller, where data from sensors in the system in the Arduino Uno will be sent using NRF24L01 and received by NRF24L01 on the Wemos D1 Mini. Then the data that has been received will be processed and sent to the internet and can be monitored through the Blynk application which can see temperature conditions, air humidity and soil moisture. From the test results, the average difference obtained at a temperature reading of 0.44 ° C and air humidity of 3.2%, and when the humidity reaches >50% the solenoid valve can open automatically. The distance that can be reached when testing as far as ±20 meters can be due to the test site being blocked by walls.